The usage of antibiotic therapy for septic complications in colorectal surgery - Fuss, Julia; Voloboyeva, Anna; Polovyj, Victor; Yaremkevych, Roksolana (Journal of Education, Health and Sport, 2021)
Over the past few decades, surgeons have made many attempts to reduce the incidence of surgical site infections (SSI) after elective colorectal surgery. Routine faecal diversion is no longer practiced in elective colonic surgery and mechanical bowel preparation is on the verge of being eliminated altogether. Intravenous antibiotics have become the standard of care as prophylaxis against SSI for elective colorectal operations. However, the role of antibiotics is still being debated. The aim of the study was to reduce the proportion of antibiotic-resistant strains of pathogens of infectious complications in colorectal surgery by optimizing the use of antimicrobial drugs. Method: We analyzed data of 135 patients who were operated for colorectal cancer in our general surgery department in between 2019 and 2021. Age, gender, body mass index, presence of chronic pulmonary disease, surgery duration, disease location (colon or rectum), and surgeon volume were evaluated for associations with the development of superficial or deep surgical site infection. Results: All parameters were found to be significant for the development surgical site infection except sex. Cut-off values were 63.5 years for age, 167.5 minutes for surgery duration. Conclusion. The introduction of strict monitoring of compliance with the protocols of antibiotic prophylaxis and antibiotic therapy at the level of a separate surgical unit in a multidisciplinary hospital improves conditions for the rational use of antimicrobial drugs.